Children in Digital Age – Polish Perspective - Gryszczyńska, Agnieszka (Children in Digital Age, 2025)
Abstract:Internet usage among children and young people offers both advantages and potential risks. These diverse risks have consequences across various areas of life – physical, psychological, and social – and, therefore, require differentiated regulatory, organisational, and educational responses. This chapter examines the regulations in Poland concerning the safeguarding of children in cyberspace. It investigates the principles of safeguarding children under civil, administrative, and criminal law. The study verifies the hypothesis of the completeness and consistency of measures to protect children from new threats arising from modern technologies and widespread Internet access. The legal framework for safeguarding children and the roles of relevant agencies are outlined. Special attention is given to the capabilities of the Ombudsman for Children, the Dyżurnet team operating within the Scientific and Academic Computer Network, and law enforcement bodies specialising in the combating of cybercrime, including child sexual abuse material. To improve the efficiency of combating cybercrime, including offences committed against children, specialised units in the police and prosecutors’ offices have been established. In 2022, the police established the Central Bureau for Combating Cybercrime, while the National Public Prosecutor’s Office created the Department for Cybercrime and Informatisation, as well as cybercrime units in selected circuit and regional prosecutors’ offices. Amendments to the Sexual Offences Threat Act have also been introduced, providing a more comprehensive approach to child protection. It is only through the application of these regulations over time that their efficacy in enhancing children’s online protection can be ascertained. To ensure an adequate level of protection for children’s rights in cyberspace, specific regulations have been analysed regarding the development of digital competences in Poland, including the Digital Competence Development Programme. Importantly, only appropriate education and the development of digital competences, including incident response and corresponding attitudes, can ensure an adequate level of protection for children’s rights in cyberspace. Keywords: legal child protection, cyberspace, cybercrime, child sexual abuse material, cyberstalking, FOMO, grooming